1997
DOI: 10.1254/jjp.74.99
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lecithinized-Superoxide Dismutase on the Rat Colitis Model Induced by Dextran Sulfate Sodium.

Abstract: ABSTRACT-Lecithinized-superoxide dismutase (PC-SOD), which is synthesized with a lecithin derivative bound covalently to recombinant human Cu,Zn-SOD, has a longer half-life in blood and higher cell affinity than unmodified SOD. The effects of PC-SOD were evaluated using the rat ulcerative colitis model induced by 3% dextran sulfate sodium. Intravenous injection of rats with 0.5 or 1 mg/kg of PC-SOD suppressed the progression of bloody stools, the formation of erosion, and the infiltration of the colon with inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…2A, PC-SOD produced the maximum beneficial effect at 1.5 to 3 kU/kg, whereas higher doses (6 -12 kU/kg) had no significant effect on DAI. A similar bell-shaped profile has also been reported in a rat model of DSS-induced colitis (Hori et al, 1997). In the case of colon shortening and colonic MPO activation, the maximal effect was again observed in response to 1.5 to 3 kU/kg PC-SOD (Fig.…”
Section: A Comparison Of the Effect Of Pc-sod And U-sod On Dss-inducesupporting
confidence: 82%
See 2 more Smart Citations
“…2A, PC-SOD produced the maximum beneficial effect at 1.5 to 3 kU/kg, whereas higher doses (6 -12 kU/kg) had no significant effect on DAI. A similar bell-shaped profile has also been reported in a rat model of DSS-induced colitis (Hori et al, 1997). In the case of colon shortening and colonic MPO activation, the maximal effect was again observed in response to 1.5 to 3 kU/kg PC-SOD (Fig.…”
Section: A Comparison Of the Effect Of Pc-sod And U-sod On Dss-inducesupporting
confidence: 82%
“…In phase I clinical studies, intravenously administered PC-SOD (40 -160 mg) had a terminal half-life of more than 24 h, with good safety and tolerability (Broeyer et al, 2008;Suzuki et al, 2008a). Furthermore, intravenously administered PC-SOD ameliorated dextran sulfate sodium (DSS)-induced colitis in rats, an IBD-related colitis animal model (Hori et al, 1997), suggesting that PC-SOD is effective for the treatment of IBD patients. In fact, recent published results of phase II clinical study have shown that intravenously administered PC-SOD (40 or 80 mg) significantly improved the disease activity index (DAI) scores of UC patients (Suzuki et al, 2008b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used PC-SOD, a derivative of SOD with higher stability in plasma and a higher affinity for tissue, which shows greater therapeutic effects than SOD in animal models of various inflammatory diseases, such as IPF, colitis, focal cerebral ischemic injury, and spinal cord injury-induced motor dysfunction (Hori et al, 1997;Tamagawa et al, 2000;Ishihara et al, 2009;Tanaka et al, 2010). We have clearly shown that PC-SOD ameliorates pulmonary emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it also reduced the increase of WBC, which is a characteristic of the acute fulminating type of ulcerative colitis. In a recent study, we suggested that an allergic-like reaction occurred in this model because neutrophils and eosinophils infiltrated the colonic mucosa (8). Bleeding was observed in the area of erosion.…”
Section: Discussionmentioning
confidence: 66%